El porqué de que bebamos alcohol tiene sus raíces en nuestra evolución - Carrigan, Matthew A. (Pontificia Universidad Católica del Perú, 2016)
We have resurrected ancient enzymes from our primate ancestors and identified several mutations occurring approximately 10 million years ago that endowed our ancestors with an enhanced capacity to metabolize ethanol.  This episode of enzyme evolution coincided with a global climate change associated with shrinking African forests and our ancestor’s transition from an arboreal lifestyle to a terrestrial lifestyle where highly fermented fruit is more common. These studies suggest that the evolution of our ancestor’s enzymes may have enabled our ancestors to exploit an alternative source of nourishment during a time when food was scarce.

Gracias a la resurrección de varias enzimas de nuestros antepasados primates se han identificado varias mutaciones que ocurrieron hace, aproximadamente, 10 millones de años, las cuales le confirieron a nuestros antepasados una capacidad mucho mayor para metabolizar etanol. Este episodio de evolución enzimática coincidió con un cambio climático global asociado con la reducción de los bosques africanos y la transición de nuestros antepasados de un estilo de vida arbórea a un estilo de vida terrestre en el cual la fruta altamente fermentada era más común. Estos estudios sugieren que la evolución de las enzimas de nuestros antepasados pueden haberles permitido explotar una fuente alternativa de alimento cuando la comida era escasa.
The reason we drink alcohol is rooted in our evolution
Keywords: Etanol; Alcohol deshidrogenasa; ADH2; ADH4; https://purl.org/pe-repo/ocde/ford#1.04.00